Prospective Analysis of the Role of Actors in the Formulation Strategy for Fisheries Development in Purworejo Regency - Maulana Ihsan Yusufi Suyatno; Rahmania Mustahidda; Dhian Andanarini Minar Savitri (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
The aim of this research is to find out how stakeholders participate in making fisheries development strategies in Purworejo. This study was conducted from January to April 2024 in Purworejo Regency. Mactor analysis is an analytical approach that provides various tools and analyzes that are useful for obtaining information and combining situations from several simple inputs about the problem being analyzed. All parties involved in developing the fisheries sector in Purworejo Regency. Data was obtained through interviews and focused discussions. Stakeholders with high role and influence and low dependency (located in quadrant I or top left). These factors are the main actors in the fisheries business in Purworejo Regency. Some of the stakeholders in quadrant II are actors who have significant influence but are also very dependent on them. To increase influence and reduce dependence on stakeholders in quadrants III and IV.